Penerapan Pembelajaran Mind Mapping Untuk Meningkatkan Hasil Belajar IPA Kelas VIII H SMPN I Gondang Mojokerto - Pramuni, Betty Endang (JoEMS (Journal of Education and Management Studies), 2022)
This research aims to increase the activity and learning outcomes of class VIII H students on the material of the human respiratory organs. When learning shows that there are still many students who think that this material is not important, resulting in low learning outcome. One effort to improve learning outcomes is to evaluate the learning model that has been used so far. Furthermore, researchers apply the Mind Map learning model which is expected to increase learning activities and learning outcomes. This type of research is Classroom Action Research with the subject of class VIII H students as many as 31 students. The results showed that learning activities in the aspect of asking questions increased by 65.32% to 82.26%, the active aspect of discussing with groups by 76.61% increased to 85.48%, the aspect of summarizing teacher explanations was 68.54% increased to 83.06%, aspects in writing discussion results by 68.54% increased to 91.12, aspects in drawing mind mapping by 79.03% increased to 83.87%. So that there is an increase in the percentage of student learning activities from cycle I to cycle II.